The prophetic literature - Sweeney, Marvin A. 1953- (Nashville, TN Abingdon Press, 2005)
The Prophets in Jewish and Christian Scripture -- Reading prophetic books -- The book of Isaiah -- The book of Jeremiah -- The book of Ezekiel -- The book of the twelve Prophets
The Prophets in Jewish and Christian Scripture -- Reading prophetic books -- The book of Isaiah -- The book of Jeremiah -- The book of Ezekiel -- The book of the twelve Prophets
The Prophets in Jewish and Christian Scripture -- Reading prophetic books -- The book of Isaiah -- The book of Jeremiah -- The book of Ezekiel -- The book of the twelve Prophets. - Includes bibliographical references (p. 221-232) and index
Archivierung prüfen
Keywords: Bible -- Criticism, interpretation, etc; Bible -- O.T. -- Prophets -- Criticism, interpretation, etc